2011
DOI: 10.3109/08880018.2011.572963
|View full text |Cite
|
Sign up to set email alerts
|

Upper Age Limits for Accessing Pediatric Oncology Centers in Italy: A Barrier Preventing Adolescents with Cancer from Entering National Cooperative AIEOP Trials

Abstract: A limited proportion of adolescents with cancer currently receives treatment at pediatric oncology centers and this factor is considered one of the possible explanations for the lack of improvement in survival trends observed over the years in this age group. The adoption of inflexible upper age limits for admitting patients to pediatric units may help to explain this situation. This paper reports the results of a national survey on adolescents' access to, and age limits adopted by, Italian pediatric oncology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 16 publications
0
28
0
2
Order By: Relevance
“…However, referral to pediatric oncology facilities may be limited in many cases by inflexible upper age limits for admitting patients to pediatric units or enrolling them in clinical trials. A recently launched survey revealed that many Italian children's centers set upper age limits at 16, 15, or even 14 years old 23 (and such centers may have difficulty coping with the two above-described paratesticular RMS patients). The results of this survey would suggest that raising these upper age limits may make pediatric oncology centers more readily accessible to adolescents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, referral to pediatric oncology facilities may be limited in many cases by inflexible upper age limits for admitting patients to pediatric units or enrolling them in clinical trials. A recently launched survey revealed that many Italian children's centers set upper age limits at 16, 15, or even 14 years old 23 (and such centers may have difficulty coping with the two above-described paratesticular RMS patients). The results of this survey would suggest that raising these upper age limits may make pediatric oncology centers more readily accessible to adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this survey would suggest that raising these upper age limits may make pediatric oncology centers more readily accessible to adolescents. 23 As for the age limits for entering clinical trials, all AIEOP protocols are currently open up to 18 or 21 years of age, and the EpSSG protocol for RMS is open up to 25 years of age. But raising the upper age limits for pediatric protocols can only truly help if adult patient groups are included in the project (as, for example, adult physicians may not otherwise hear about the trial).…”
Section: Discussionmentioning
confidence: 99%
“…The limited access of these patients to referral centers and their inadequate inclusion in clinical trials have probably played a significant part in the limited improvement in their outcomes compared with what has happened in other age groups (4, 7, 15, 26–29). When developing innovative programs, special attention must be paid to economic entailments and institutional support; acceptance as a standard of care is fundamental to the establishment of structured programs.…”
Section: Models Of Carementioning
confidence: 99%
“…Studies exploring trial inclusion rates have identified structural and organisational factors that prohibit AYA from entering studies . More recently, the characteristics of AYA, the influence of healthcare professionals and trial design have also been implicated . While these are helpful in assisting trialists to identify underrepresented populations, this evidence has done little to improve the recruitment of AYA to research.…”
Section: Introductionmentioning
confidence: 99%